Dynamic Functional Connectivity Within the Fronto-Limbic Network Induced by Intermittent Theta-Burst Stimulation: A Pilot Study - Tang, Yingying; Jiao, Xiong; Wang, Junjie; Zhu, Tianyuan; Zhou, Jie; Qian, Zhenying; Zhang, Tianhong; Cui, Huiru; Li, Hui; Tang, Xiaochen; Xu, Lihua; Zhang, Ling; et al. (Frontiers in Neuroscience, 2019)
Purpose: The utility of transcranial magnetic stimulation (TMS) is growing rapidly in both neurocognitive studies and clinical applications in the decades. However, it remains unclear how the responses of the stimulated site and the site-related functional network to the external TMS manipulation dynamically change over time. Methods: A multi-session combing TMS-fMRI experiment was conducted to explore the spatiotemporal effects of TMS within the fronto-hippocampal network. Ten healthy volunteers were modulated by intermittent theta-burst stimulation (iTBS) at a precise site within the left dorsolateral prefrontal cortex (DLPFC, MNI coordinate [-44 36 20]), navigated by individual structural MRI image. Three-session resting-state fMRI images were acquired before iTBS (TP1), immediately after iTBS (TP2) and 15 minutes after iTBS (TP3) for each participant. Twelve regions of interests (ROIs) within fronto-hippocampal network were chosen including the bilateral superior frontal gyrus (SFG), bilateral middle frontal gyrus (MidFG), bilateral triangularis (IFG_tri) and pars opercularis (IFG_oper) parts of inferior frontal gyrus, medial frontal cortex (MedFC), anterior cingulate gyrus (AC) and bilateral hippocampus. Voxel-wise fractional amplitude of low-frequency fluctuation (fALFF) and ROI-to-ROI functional connectivity (FC) were compared among TP1, TP2 and TP3. Results: The immediate iTBS effect was observed at the stimulated site. FC was decreased between the left MidFC / SFG and left hippocampus and between the left MidFG and left SFG at TP2 as compared to at TP1 (all FDR-p<0.05). The relatively long-term iTBS effect transmitted with decreased FC between the left IFG and left hippocampus (FDR-p<0.05) at TP3 than at TP1. Meanwhile, fALFF values in the bilateral MidFG and AC (all p<0.05) were significantly decreased at TP3 as compared to those at TP2, but fALFF values in the left IFG increased (all FDR-p<0.05). Conclusions: By combining TMS and fMRI, it becomes possible to track the spatiotemporal dynamics of TMS after-effects within the fronto-hippocampal network. Our findings suggested that the iTBS effect dynamically changed over time from the local neural activation at the stimulated site to its connected remote regions within the fronto-hippocampal network.